Implementasi Model View Presenter dan Object Relational Mapping NHibernate pada Aplikasi eStop Card berbasis Web (Studi Kasus: PT. XYZ Jakarta) - Alessandro Christoforus Baramuli; Adi Nugroho; Angela Atik Setiyanti (Universitas Kristen Duta Wacana, 2013)
The development of technology has shown significant progress, especially in application architecture design pattern. Model View Presenter (MVP) pattern is one of the most important pattern used for extracting business logic outside of User Interface (UI) elements and by that enabling unit test without the need testing tools, and specifically geared towards for page event model in ASP.NET. Together with MVP, Object Relational Mapping (ORM) NHibernate is implemented to build a web base application. ORM is a technique to map an object to a database. It can be concluded that the implementation MVP and ORM to build a web base application resulting a well-performed and easily maintained application as well as it effectiveness when performing unit test, and also a clear separation layer between model, view, presenter.